BERSIH MELAYANI UMAT HINDU MENUJU SUMBER DAYA MANUSIA BERKUALITAS (PERSPEKTIF FILSAFAT HINDU) - I KETUT SUBAGIASTA (Purwadita : Jurnal Agama dan Budaya, 2017)
This article entitled “The Clean Service of Human Mankind of Hindu Concern for Human Resources be Quality Perspective Philosophy of Hindu”. Main description of this article about honest service for enlightenment spiritual Hindu human mankind, the openness in creation young generation of Hindu, the allegiance in life of the household, the balanced in dynamic of reality of  working,  and  persevering  study  in  the  period  of  the  yong  generation.  Then  described  also about  the  become  Hindu  generation  which  be  wide  perception,  become  generation  ready  as competitor, become the generation of Hindu be skillful, become the Hindu generation the best prestige, and become the Hindu generation militant.